Lanthanides and other spectral oddities in a Centauri: Ce III, Nd III, KrII, and broad absorption features - Cowley, C. R. (2010)
Context. There is considerable interest in the helium variable a Cen as a bridge between helium-weak and helium-strong CP stars. Aims. We investigate Ce iii and other possible lanthanides in the spectrum the of hottest chemically peculiar (CP) star in which these elements have been found. A Kr ii line appears within a broad absorption which we suggest may be due to a high-level transition in C ii. Methods. Wavelengths and equivalent widths are measured on high-resolution UVES spectra, analyzed, and their phase-variations investigated. Results. New, robust identifications of Ce iii and Kr ii are demonstrated. Nd iii is likely present. A broad absorption near λ4619 is present at all phases of a Cen, and in some other early B stars. Conclusions. The presence of lanthanides in a Cen strengthens the view that this star is a significant link between the cooler CP stars and the hotter helium-peculiar stars. Broad absorptions in a Cen are not well explained.